Design Of Cascade NP/PI Controller For Cutting Force Compensation Of Ball Screw Driven System - Anang, Nur Amira (2018)
This research explores control strategies for compensation on effect of cutting forces on accuracy of positioning table of a milling machine using a controller named cascade NP/PI. The control structure of cascade NP/PI controller was based on the conventional cascade P/PI controller with an add-on module of a nonlinear function. The system stability was guaranteed before the nonlinear parameters such as rate of variation of nonlinear gain (KO) and maximum value of error (emax) were determined. Cutting forces exist during milling cutting process, exert additional force on the drive system of the positioning table that if left uncompensated would impact on the accuracy and precision of the system. Therefore, it is crucial that the negative effect of these cutting forces are damped so as to retain the positioning accuracy and precision of the drive system. Cutting forces contain harmonics frequencies depending on the spindle speed rotations. An efficient controller that is able to damp these harmonics content is then desired. In this research, another two controllers were designed, namely, PID controller and cascade P/PI controller to compared the results with the proposed cascade NP/PI controller. The controllers’ performances were analysed numerically and validated experimentally on the X-axis of an XY ball screw driven positioning table using cutting forces measured at depth of cut of 0.2mm and 1mm and spindle speed rotations of 1500rpm, 2500rpm and 3500rpm. Analyses were performed on each of these controllers in terms of maximum tracking error, Root Mean Square (RMS) of tracking error and Fast Fourier Transform (FFT) of errors. Results of maximum tracking error showed that cascade NP/PI controller produced the lowest percentage error 0.25% compared to PID and cascade P/PI controller with 0.26% and 0.61% respectively whilst results on error reduction based on RMS of error showed that the proposed cascade NP/PI controller outperformed PID and cascade P/PI controller by as much as 62.1% and 6.3% respectively. Furthermore, spectrum analysis showed that cascade NP/PI controller has successfully compensated the negative effect of the cutting forces with the highest error reduction in term of damping of the peak frequencies by as much as 42.53% and 27.54% compared to PID and cascade P/PI controller respectively. As the research outcome, a review on precise positioning control strategy has been published in 2017. In 2018, the study on the nonlinear function implementing on PID and cascade P/PI controllers have been done and published in journal and book chapter.